Aqueous enzymatic extraction of polyunsaturated fatty acid–rich sacha inchi (Plukenetia volubilis L.) seed oil: An eco-friendly approach. (November 2020) - Nguyen, Hoang Chinh; Vuong, Dat Phu; Nguyen, Ngoc Thanh Tam; Nguyen, Nguyen Phuong; Su, Chia-Hung; Wang, Fu-Ming; Juan, Horng-Yi
Abstract: Sacha inchi seeds are a potential source of natural oil rich in essential polyunsaturated fatty acids and have various nutraceutical and health benefits. This study developed an aqueous enzymatic extraction process for eco-friendly extracting sacha inchi seed oil. The activities of different enzymes (proteases and cellulase) in the extraction process were evaluated. Among the tested enzymes, papain exhibited the highest extraction activity. The papain-assisted extraction was subsequently optimized through response surface methodology to yield maximum oil level. A maximum oil yield of 28.45% was obtained under the following extraction conditions: enzyme loading, 4.46%; water-to-sample ratio, 4.45 mL/g; extraction time, 4.95 h; and temperature, 38.9 °C. Under optimal extraction conditions, papain could be repeatedly used for extraction. This study indicates that papain is a potential protease and that aqueous enzymatic extraction is an eco-friendly and efficient process for extracting beneficial oil from sacha inchi seeds. Highlights: Papain was the most potent for extracting oil from sacha inchi seeds. A maximum oil yield of sacha inchi seeds was 28.45%. Papain could be reused at least 5 times for oil extraction from sacha inchi seeds. Aqueous papain-assisted extraction is an ecofriendly method for oil extraction.